Implementation of gamified mobile application to increase engagement and society inclusiveness by integrating strategy game and E-Quiz / Rosfuzah Roslan - Roslan, Rosfuzah (2021)
The COVID-19 outbreak has globally affected many countries and sectors, including education. According to a UNESCO report, more than 1 billion students were affected by educational institutions closures in 106 countries, hence forcing the 'new norm' of teaching and learning environment. E- learning and mobile learning (M-learning) are the main choices that also create welcoming communities, building an inclusive society, and achieving education for all. Gamification in educational mobile applications serves as an added value in mobile learning to the instilled sense of enjoyment in educator and learners' interactions. It also leverages students' desires for achievement, competition, status, and to be part of an inclusive social community to increase engagement. Incorporating strategy games in educational mobile applications posed several benefits such as creating continuance usage desire among users, enhance motivation among disengaged learners, encourage strategic thinking, promotes healthy competition, improve self-directed learning and independent thinking, foster collaboration, create a safe environment for learning through experimentation and trial and error, also it helps develop virtuous qualities (patience and persistence) among learners. Meanwhile, an e-quiz which is a form of a quick formative assessment tool helps in the implementation of the 'testing effect' or 'retrieval practices' activity for learners. Implementing progressive gamified e-quiz with a strategy game in learning through mobile technology, supports the current or 'new norm' needs of distance learning while expanding society inclusiveness. This research highlights the development and usage of a gamified e-quiz mobile application whose unique feature is the 'reward' system that is interconnected with a progressive strategy game to enhance engagement and inclusive education in the 'new norm' teaching and learning environment.